Personalidad, inteligencia emocional y afectividad en estudiantes universitarios de áreas empresariales Implicaciones para la formación de líderes (2010)
The purpose of this study was to describe the personality, the affect and the emotional intelligence of 422 business students throughout their training process. The Personality Inventory NEO-FFI of Costa & McCrae (1994), the Spanish versions of TMMS-24 (adapted by Fernández-Berrocal, Extremera, & Ramos, 2004) and the PANAS (adapted by Sandín et al., 1999), were used. We found high levels of Neuroticism and low levels of Extraversion, Openness to Experience and Agreeableness; Emotional Intelligence achieved intermediate levels, and a predominant positive affectivity. The neuroticism was increased in some semesters, the Openness to Experience and Conscientiousness although all of them had low levels, tended to increase during the formation. The participants are characterized by positive emotions, which does not seem to depend on the formation processes but their personal characteristics. These findings are discussed in relation to the training of business leaders.